A ?constrain and move? approach to distributed object manipulation. - Ahmadabadi, M.N.
Studying the system dynamics, this research is an attempt to understand and design the basic robot behavior, information system, and distributed cooperation strategies required by a group of cooperative behavior-based mobile robots for handling an object. A new concept to develop distributed cooperation strategies to carry a load is introduced. In this method, the task of transferring the object is divided into two independent executable subtasks: constraining and moving the load. Each subtask is assigned to a group of distributed mobile robots. Based on this idea (constrain-move concept), two distributed cooperation strategies to turn the object about a fixed point and to move it along a straight line are introduced. The constrain-move concept is generalized for lifting and lowering the object. It is noted that weight of the payload can be used by the robots as a natural constraint on the object. Utilizing this natural constraint, a distributed cooperation strategy and an information system to lift and lower the object are introduced. The coordination protocols are devised in such a way that the robots can control movements of the object using their own sensory information and some static data communicated between the team members. Simulation and experimental results are given to support the proposed approach
Keywords: Cooperative behavior-based mobile robots; Distributed cooperation strategy design; Distributed mobile robots; Distributed object manipulation; Independent executable subtasks; Information system design; Robot behavior design; Static data